THE PROBLEMS OF DIVORCE IN CUMULATION AT THE RELIGIOUS COURTS BASED ON THE PRINCIPLES OF SIMPLE, FAST AND LOW COST - Elis Rahmahwati (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Religious Courts is a special Court and its specialization lies on the principles of Islamic personality. One of its absolute authorities is on the marriage, which also includes divorce cases. Divorce cases in the Religious Courts can be combined with the child custody matter, children living cost, wife living cost, and joint property, with the aim to establish the principles of simple, fast, and low cost. But in reality, it cannot be fulfilled because it would hold up the divorce process itself, which at the beginning the parties have no objection to divorce, but then become objected to the unification, such as joint property lawsuit. Thus on those kinds of cases, a legal efforts will be conduct altogether with the divorce process that included the main claim, and it took years on the process. The theory of justice based on expediency based on Mill’s opinion and a theory of the Islamic law is to bring the benefits and avoid madharat (damage). The divorce cases that being cumulated turned out bring more madharat. Stages of the trial, like mediation, can be the anticipation of the extended process. An agreement made by the parties will results in a divorce case that is simple, fast, and low cost, without any legal efforts made by the party which feel any disadvantages due to the decision given by the Judges. Keywords: cumulation divorce, religious court, mediation.